Pengembangan Onti Measures Berbasis Web dengan Pengujian Data Ontology Virus dan Penyakit - Nur Alfi Ekowati; Ika Indah Lestari; Sulistiyasni (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
The use of the ontology document in the COVID-19 case is an example where the inconsistency measure for OWL ontologies is undoubtedly needed. Ontology is a knowledge representation of semantic web technology, which is the extension of a website. The role of inconsistency measure is essential in ensuring that all information on an ontology is consistent. This research aims to develop a web-based application program, namely Onti Measures, which is an expansion of the inconsistency measures program prototype that has been created in the previous research. That prototype has multiple weaknesses, such as it is only in the form of program codes with no user interface so that the public cannot access this program. The data collection method in this research was done through literature study, while the waterfall method was used as the system development method. This research’s testing sample was ontology files for virus and disease cases served as the input of Onti Measures using 3 types of OWL reasoners. The program's outputs were the information of inconsistency values, running times, and the ontology sizes. The testing was done by employing the whitebox and blackbox testing methods.